« Le cadavre est à terre et l’idée est debout » : le souffle communard sur la scène contemporaine - Nathalie Coutelet (Cahiers d’histoire.)
The « Commune » remains a fruitful source of inspiration for many contemporary shows, less to celebrate history than to transpose the communard utopia into our current events or to glorify this popular and poetic impetus. Music and song thus hold a central place there, in order to appeal to the collective memories and to make this communard spirit sensitive. If the works include historical personalities and events, and pay particular tribute to the women’s action, they all develop, according to various scenic forms, a reflection that is both political and aesthetic on the today’s theater and society.